Impacts of Corporate Social Responsibility on Employees’ Mental Fatigue: Employees’ Ethical Perspective - Zheng, Linlin; Li, Wenzhuo; Addis, Amsalu K.; Ye, Di; Dong, Yashi (Frontiers in Psychology, 2022)
With the rise of cost of living and coronavirus disease 2019 (COVID-19) global pandemic therewithal, finding reliable measures to reduce employees’ mental fatigue has become a great challenge. In this context, scholars have mainly focused on solutions for relieving employees’ mental fatigue from the perspective of human resource management but barely from employees’ ethical perspectives and that of internal and external corporate social responsibility (CSR) and employees’ ethics. This study uses hierarchical regression analysis and attempts to formulate and analyze the relationship between CSR, perceptions of corporate hypocrisy, and employees’ mental fatigue along with the mediating role of ethical egoism and altruistic choice. It also conceptualizes models and develops various hypotheses and theoretical logic. A total of 250 questionnaires were distributed, and 176 valid responses were subsequently gathered. The results show that employees’ mental fatigue significantly reduces when either internal or external CSR has a positive impact on employees’ altruistic choice and significantly increases either internal or external CSR has a negative effect on ethical egoism. Similarly, reducing perceptions of corporate hypocrisy can enhance the positive impact of external CSR on altruistic choice, which consequently reduces employees’ mental fatigue.